Determinants of Social Entrepreneurial Intentions of University Students in South Africa - Fatoki, Olawale (Journal of Economics and Behavioral Studies, 2018)
Entrepreneurial behaviour can be predicted by intentions. The study investigated the determinants of social entrepreneurial intentions (SEI) of university students in South Africa. The study adopted a quantitative research design that involved the use of a survey. The self-administered questionnaire method was used to collect data from the survey participants. The participants in the survey were final year undergraduate students of the Department of Business Management of two South African universities. Reliability was measured using the Cronbach’s alpha. The data analysis methods for the study were descriptive statistics, principal component analysis and regression analysis. The results indicated that empathy, moral obligation, entrepreneurial self-efficacy and perceived social support are predictors of social entrepreneurial intentions. The recommendations to improve the SEI of university students focus on passive and active entrepreneurship teaching methods.
Article published in Journal of economics and behavioral studies
Keywords: Determinants; Social entrepreneurial intentions; University; Students; South Africa; Student-owned business entreprises